Analysis of Factors Affecting Local Government Financial Performance - Budi, Raden Budi Hendaris; Sastradipraja, Usman (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The financial performance of local governments (LG) in implementing regional autonomy has a central role. However, the phenomenon is that only some local governments have this financial capability. Therefore, this study examines what factors can affect financial performance. This study empirically analyzed the effect of capital expenditure, local government size, legislative size, local revenue, and audit opinion on the financial performance of local governments in districts and cities in West Java. The method used uses quantitative methods. The research data used financial reports of Regency and City Regional Governments in West Java for the period 2015 - 2022 using Purposive Sampling. A total of 216 data were analyzed using Multiple Linear Regression. The steps in this study begin with a review of literature and regulations, data collection, data tabulation, data analysis, and then reporting and publication of research results. The results showed that the size of local government, local revenue, and audit opinion had a positive effect on financial performance, while capital expenditure and legislative size did not affect financial performance. Based on the results of this study, the implication is that district and city governments in West Java must increase the size of local governments, local revenue, and audit opinion to improve their regions' financial performance. Keywords: Performance, capital expenditure, local government size, PAD, legislative size, audit opinion.